Progressão tópica e referencial em interações no contexto da atrofia cortical posterior - Silvestrin, Jordana Molinetti (Universidade do Vale do Rio dos Sinos, 2020)
Posterior Cortical Atrophy (PCA) is a rare progressive and neurodegenerative disease considered a subtype of Alzheimer's Disease (AD). The first symptom to be manifested by PCA is the impairment of visual functions; however, that pathology also compromises the use of language. Facing this pathological condition, the present research aims, in general, to verify how referential progression and topical progression in oral interactions of a person affected by PCA occurs. To do so, two analytical categories will be mobilized, the discursive topic, originating from the Conversation Analysis, and the referencing, coming from the field of Textual Linguistics, in the lights of, mainly, the theorists Jubran (1992, 2006a, 2006b, 2006c, 2006d), Koch (1990, 1997, 2002, 2008a, 2008b, 2015) and Marcuschi (1998, 2001, 2006, 2008), in order to observe the meaning-making strategies and the interactive engagement in the CPA context. The linguistic corpus of this study consists of open interviews, recorded with a participant with PCA, and the total time of the recordings that comprise the data is about 48 hours. The data are derived from the development of the research project entitled The discursive topic in the analysis of interactions of a Support Group for family caregivers of individuals with Alzheimer's Disease, coordinated by Professor Dr. Caio Mira, from the Postgraduate Program in Applied Linguistics (PPGLA), from Universidade do Vale do Rio dos Sinos (UNISINOS). The choice of excerpts to be analyzed was based on the significant occurrence of strategies used by the participant, due to their language difficulty, the intention to construct the intended referent in collaboration with their interlocutor, and the relevant occurrence of strategies that signal the management of discursive topics. The research results reveal that there is a recurrence of processes of sequencing, expansion, change and resumption of discursive topics, strategically motivated by the participant with PCA, in order to incorporate meaning into the oral text. Furthermore, it was revealed that the referencing processes constituted by the participant designate a sociocognitive-discursive construction of discursive objects established by means of negotiation processes. And, finally, through the corpus analysis, the relationship between the discourse objects and the discursive topic was pointed out.
Keywords: Tópico discursivo; Referenciação; Atrofia Cortical Posterior; Análise da conversação; Linguística textual; Discursive topic; Referencing; Posterior Cortical Atrophy; Conversation analysis; Textual linguistics; ACCNPQ::Lingüística, Letras e Artes::Lingüística